Literary Cartographies
XI, 236 p.
Keywords: Exploring narrative mapping in a wide range of literary works, ranging from medieval romance to postmodern science fiction, this volume argues for the significance of spatiality in comparative literary studies. Contributors demonstrate how a variety of narratives represent the changing social spaces of their world.